IDENTIFIKASI KORIDOR JALAN SUKUN RAYA SEMARANG DAN POTENSI REVITALISASI SHOPPING MALL BERKONSEP PEDESTRIAN WALK - Shabrina Adine Vania; Gagoek Hardiman (Jurnal Arsitektur ARCADE, 2024)
Various private housing estates have developed in Banyumanik Subdistrict, such as Taman Setiabudi Housing, Puri Perdana, Jati Raya Indah and others. Taman Setiabudi Housing is unique because the entrance to the housing estate has developed into a street market area and Pasar Minggu. This housing is located on the Sukun Raya road corridor. This corridor has developed several shops, restaurants, supermarkets, minimarkets, rows of shophouses, schools, restaurants, cafes, clothing stores, pharmacies, street vendors, salons, grocery stores, fruit and vegetable shops and gas stations. There is an abandoned building that used to be the Harmoni Supermarket, which was successful in the 1990-2000 era and closed in the 2000s. Many changes in the function of buildings into commercial buildings characterize the rapid development of the corridor into a commercial area. This research aims to reveal the characteristics of the corridor and find the design potential of developing the corridor as a pedestrian walk by revitalizing the Harmoni shopping building. The research uses survey methods, interviews, depictions of corridors, and Google Streetview to detail building types and facades. The research findings show the potential to develop the Sukun Raya corridor as a commercial area with a pedestrian walk concept by revitalizing the shopping mall.